Further studies on nitrofurantoin excretion in dog hepatic bile - Conklin, J. D. (1973)
1. Results obtained with a dog donor-recipient model indicate that following intravenous administration of nitrofurantoin sodium, nitrofurantoin is subjected to enterohepatic cycling. At least one-third of the nitrofurantoin originally excreted in the donors' bile after a nitrofurantoin dose of 3 mg/kg is reabsorbed intestinally in the recipients within 3 hours. 2. After intraduodenal administration of a nitrofurantoin suspension to dogs at doses ranging from 2 to 12 mg/kg, about 10% of the dose is recovered in bile as nitrofurantoin within 6 hours. A hydrocholeretic effect was also observed which correlated with the amount of drug administered. Both biliary drug excretion and the related hydrocholeresis appeared linearly related over the drug dose range. 3. The hydrocholeresis observed in dogs within 3 h after intravenously administered nitrofurantoin sodium, equivalent to 3 mg/kg nitrofurantoin, was at least ten times that seen following the intravenous administration of an equimolar dose of dehydrocholic acid given as its sodium salt.